Pengaruh pengetahuan peraturan perpajakan dan sanksi pajak terhadap kepatuhan wajib pajak kendaraan bermotor - Rachmawati, Intan; Rachman, Andry Arifian (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
Data on the proportion of SAMSAT Rancaekek taxpayer compliance for 2021 shows that there has been a decline due to economic conditions that have not recovered 100% from the impact of the Covid-19 pandemic. This study aims to examine how the influence of tax information and tax sanctions on taxpayer compliance in the field of motor vehicle taxation. Researchers used the slovin formula and a simple random sampling mechanism to collect information from 100 people. Data collection from taxpayers at SAMSAT Rancaekek used open and closed questionnaires for this study. This study uses a quantitative methodology because of the numbers involved. Researchers screened the initial data and found 14 outliers; Hence, 86 respondents were included for statistical analysis. IBM SPSS version 26 was used to perform multiple linear regression analysis and descriptive statistics for this study. The findings show that the taxpayer's understanding of tax regulations and tax sanctions simultaneously and partially influences taxpayer compliance with motorized vehicle tax at SAMSAT Rancaekek.